Students’ Perception of Mobile Applications in Calculus Learning - Ainul Maulid bin Ahmad; Mu’azah Bt. Md. Aziz; Muhammad Shahrizan B. Shahrudin (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Mathematics is a crucial subject that students learn from primary school onward. However, some students have a negative perception of mathematics, considering it difficult and tedious, especially among Generation Z, who have grown up in a world where information is readily available at their fingertips. So, traditional teaching methods may not be very effective. This study aimed to determine students’ perceptions of mobile applications in calculus learning. The study involved 35 students from a private university in Kedah. This quantitative study utilizes a survey method and employs a questionnaire as the research instrument. The perception questionnaire is divided into four categories: attractiveness, effectiveness, relevance, and motivation. Based on the research findings, this study concludes that students had a positive perception of four aspects—attractiveness, effectiveness, relevance, and motivation— when using a mobile application for calculus learning.